First report of palpebral conjunctival inflammatory nodule associated with Demodex species - Ying Li; Ga Eon Kim; Kyung Chul Yoon; Won Choi (Indian Journal of Ophthalmology, 2018)
Demodex mite infestation of the palpebral conjunctiva as focal inflammatory nodule has been not reported. A 46-year-old man presented with lower palpebral conjunctival nodules in his left eye. Slit-lamp examination showed focal inflammatory nodules at the inferior palpebral conjunctiva accompanied by conjunctival hyperemia and purulent secretion. Excisional biopsy of this lesion was performed. Pathological evaluations revealed inflammatory granuloma associated with Demodex species in the palpebral conjunctiva. This is the first report of Demodex-related palpebral conjunctival inflammatory nodule and may be helpful in future Demodex-associated studies.